PENGEMBANGAN LAYANAN UMPAN BALIK PADA FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS ATMA JAYA MAKASSAR - Syarif, Adi Chandra; Boksman, Tommy (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2019)
The main goal of this thesis is to develop a mobile-based course monitoring system at Atma Jaya Makassar University Faculty of Information Technology, which focuses on feedback services for stakeholders. This research was carried out using waterfall methodology, which consists of a number of stages carried out systematically. Through this research, it is known that the mobile-based feedback service can improve the monitoring function in lecturing process through transparency and availability of information for stakeholders, as well as feedback to be evaluated in conducting lectures.